Economic Inequality of the Regions and Imbalances of the Russian Budget System - Sabitova, N. M.; Shagiahmetov, M. R.; NIvanova, N. G. (International Journal of Economics and Financial Issues, 2016)
In spite of economic and social progress economic and social inequality in the world still exists. It can be considered in different aspects: between different population groups, countries, regions of the certain countries. Problems of economic inequality of the Russian Federation regions, as well as its conditioning factors are being reviewed in this article. Calculations proving that inequality in economic development of the Russian regions is decreasing insignificantly are listed here. This inequality causes differentiation of the taxable capacity and fiscal capacity that affect stability of the budget system of the Russian Federation. An alignment mechanism for the level of fiscal capacity based on the subsidies is being used in order to decrease the level of fiscal capacity of the Russian subjects. The calculations contained in the article demonstrate that alignment only minimizes this inequality. It is being proved that solution of the problem of differentiation of the regions' level of economic development is to be performed using set of measures decreasing these gaps. Keywords: economic inequality, Russian regions, economic development, Gross Regional Product, taxable capacity, index of budgetary expenditures, subsidies. JEL Classifications: I210; E660; H520